The influence of marketing content on brand awareness and its impact on citamin product purchase decisions - Rachman, Muhammad Arief; Fauziah Eddyono (SEAN Institute, 2024)
This research has the objective to examine the direct impact of marketing content on brand awareness, the influence of brand awareness on purchasing decisions, the direct impact of marketing content on purchasing decisions, as well as the impact of marketing content on brand awareness and its subsequent effect on purchasing decisions. The research employs a descriptive quantitative research method with a sample size of 88 respondents. The outcomes indicate that marketing content significantly influences brand awareness, brand awareness directly affects purchasing decisions, and marketing content also directly affects purchasing decisions. Moreover, marketing content exerts a direct influence on brand awareness and subsequently affects purchasing decisions. The R-square value for the brand awareness variable demonstrates that content marketing accounts for 33.9% of the variance, suggesting the possibility of additional variables in future research.